Physicians' financial incentives and treatment choices in heart attack management - Dominic Coey (Quantitative Economics, 2015)
Using a large set of private health insurance claims, we estimate how physicians' financial incentives affect their treatment choices in heart attack management. Different insurance plans pay physicians different amounts for the same services, generating the required variation in financial incentives. We begin by presenting evidence that, unconditionally, plans that pay physicians more for more invasive treatments are associated with a larger fraction of such treatments. To interpret this correlation as causal, we continue by showing that it survives conditioning on a rich set of diagnosis and provider-specific variables. We perform a host of additional checks to verify that differences in unobservable patient or provider characteristics across plans are unlikely to be driving our results. We find that physicians' treatment choices respond positively to the payments they receive, and that the response is quite large. If physicians received bundled payments instead of fee-for-service incentives, for example, heart attack management would become considerably more conservative. Our estimates imply that 20 percent of patients would receive different treatments, physician costs would decrease by 27 percent, and social welfare would increase.
Keywords: 330; Physician incentives; physician treatment choices; health insurance; heart attack management; fee-for-service payments